Epidemiological and etiological characteristics of hand, foot, and mouth disease in Wuhan, China from 2012 to 2013: Outbreaks of Coxsackieviruses A10. Issue 6 (9th March 2015) - Yang, Qin; Ding, Jinya; Cao, Junhao; Huang, Qianchuan; Hong, Chun; Yang, Bin
<x xml:space="preserve">Abstract</x> Hand‐foot‐mouth disease (HFMD) is a common infectious disease which often occurs in young children. It is caused by enteroviruses, most commonly enterovirus71 (EV71) and Coxsackievirus A16 (CVA16). The present study focuses on the molecular epidemiology of the pathogen of HFMD in the Wuhan region of China during the period 2012 to 2013. A total of 463 viruses were isolated from throat swab of 3, 208 HFMD patients and analyzed by quantitative RT‐PCR with all sets of specific primers for EV71, CVA16, and pan‐enterovirus. Of the 463 viruses, 111 (21.2%) were EV71, 52 (9.6%) were CVA16, and 300 (69.2%) were pan‐enterovirus. In pan‐enterovirus isolations 190 (52.8%) were CVA10, 50 (13.9%) were CVA4, 30 were CB2, 17 were CB3, 13 were CB5 identified by VP4 gene sequencing. Eleven EV71 isolates were complete genome sequenced and phylogenetic analysis revealed that the EV71 strains that circulated in Wuhan belonged to the C4 subgenotype. Among the 190 CVA10 isolations, 187 CVA10 strains have the same nucleotide sequence, the other three CVA10 strains belongs to another type of nucleotide sequence. Phylogenetic analysis based on 19 CVA10 isolations suggested that they belonged to the clade of Chinese strains, but form different clusters isolated from Japan, Europe. This study showed that EVA71 and CVA16 were detected as the predominant viruses (>60%) in 2012 and the total reported HFMD cases attained a peak in June and July. In contrast, CVA10 was also detected during April 2012 and replaced EVA71 and CVA16 as the major HFMD‐associated pathogen from May 2013. J. Med. Virol. 87:954–960, 2015. © 2015 Wiley Periodicals, Inc.